Endothelin inhibitors for advanced prostate cancer - HOLLYWOOD, DONAL; FOLEY, RUTH (John Wiley, 2011)
This is the protocol for a review and there is no abstract. The objectives are as follows: Our review aims to determine the effectiveness and adverse effects of endothelin inhibitors for advanced prostate cancer. The primary objectives are to assess the effect of endothelin inhibitors on overall survival, prostate cancer-speci?c survival, and progression-free survival. The secondary objectives are to determine: 1. the frequency of adverse events; 2. the effect of treatment on target lesions identi?ed by radiological imaging; 3. the effect of treatment on molecular biomarkers, including PSA and bone alkaline phosphatase; 4. the impact on quality of life.
PUBLISHED
Keywords: Oncology; Prostate cancer